Nilai Pengetahuan dan Sikap Peduli Lingkungan Mahasiswa Pendidikan Geografi di Universitas Prof. Dr. Hazairin, SH Bengkulu - Zairin Zairin; Muhammad Alfi; Warsa Sugandi Karman (Universitas Prof. Dr. Hazairin, S.H, 2023)
This study aims to determine the value of the knowledge and attitude of caring for the environment for students of geography education at the University of Prof. Dr. Hazairin, S.H. Bengkulu. This research was conducted after implementing the Population and Environmental Education course which had the outcome of planting mangroves on the coast of Bengkulu. The sample of the study population was 75 respondents with 20 questionnaire items. The time of the research starts from May 2023 to August 2023. The measurement scale in this study is the Likert scale. Data collection through literature study, interviews, questionnaires, and documentation. This research was conducted by distributing questionnaires and interviews. Based on the results of questionnaire data processing, the knowledge value of university geography education students Prof. Dr. Hazairin, SH has a very high frequency with a total score of 86%. Furthermore, the environmental care attitude of university geography education students, Prof. Dr. Hazairin, SH also has a high frequency with a total score of 89%. It can be concluded that the value of the knowledge and attitude of caring for the environment in geography education students at the University of Prof. Dr. Hazairin, SH is very kind Keywords: Knowledge, Environmental Care Attitude, Students